2020
DOI: 10.1016/j.radonc.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of radiomic features to inter-observer variability and image pre-processing in Apparent Diffusion Coefficient (ADC) maps of cervix cancer patients

Abstract: a b s t r a c tPurpose: The aims of this study are to evaluate the stability of radiomic features from Apparent Diffusion Coefficient (ADC) maps of cervical cancer with respect to: (1) reproducibility in inter-observer delineation, and (2) image pre-processing (normalization/quantization) prior to feature extraction. Materials and methods: Two observers manually delineated the tumor on ADC maps derived from pretreatment diffusion-weighted Magnetic Resonance imaging of 81 patients with FIGO stage IB-IVA cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…As expected, this left-sided shift was not observed with the quantization range of mean ± 2 SD or mean ± 3 SD, because the effect of the outliers truncated with these settings. Although the quantization range of mean ± 3 SD was used for outlier removal 30 and provided more reliable information, the effects of outliers could not be fully removed by the normalization process, as demonstrated in the current study. Therefore, to achieve reliable RFs, outlier control should be carefully performed as part of the image segmentation process.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…As expected, this left-sided shift was not observed with the quantization range of mean ± 2 SD or mean ± 3 SD, because the effect of the outliers truncated with these settings. Although the quantization range of mean ± 3 SD was used for outlier removal 30 and provided more reliable information, the effects of outliers could not be fully removed by the normalization process, as demonstrated in the current study. Therefore, to achieve reliable RFs, outlier control should be carefully performed as part of the image segmentation process.…”
Section: Discussionmentioning
confidence: 88%
“…Outlier control is an important factor influencing RFs 29 , although to our knowledge, there have been only limited studies evaluating how outliers affect the reliability of RFs 16,30 . Our simulation results demonstrated that the unintended inclusion of outliers within ROIs seems to have the strongest impact on the GLCM and GLRLM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies show the jarring results concerning the prognostic value of ADC in cervical cancer, some documenting poorer prognosis with a lower ADC value [59]. The VOI delineated on the T2W image could have been extrapolated on the ADC maps, to extract the radiomic features on ADC images as done in previous studies [60], but the additional normalization and binning done was beyond the scope of this study. Undeniably, a better understanding of the core spatial heterogeneity could be offered by VOI delineation and analysis of ADC imaging; however, the above factors with resource and time constrains prevented us from exploring this particular aspect, thus limiting the usefulness into routine clinical practice [61].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the intratumor heterogeneity regarding water diffusion is deserved to be explored by radiomics based on DWI with multiple b values. A recent study reported that 63% of ADC-based radiomics features without image normalization were reported to have good inter-observer agreement in patients with cervical cancer (31). In the present study, we found a higher proportion of radiomics features (83%) with good inter-observer agreement, which may be attributable to differences in tumor type and size and image quality.…”
Section: Discussionmentioning
confidence: 99%